Pengaruh Struktur Modal, Profitabilitas, Likuiditas, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan pada Perusahaan Consumer Goods yang Terdaftar di BEI Periode 2008-2012 - Prisilia, Indah; Wijaya, Errin Yani; ', Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the significant impact of capital structure, profitability, liquidity, and Insider Ownership toward firm value in consumer goods companies which are listed since 2008 up to 2012. Population in observational it is all consumer goods companies listed on Indonesian’s Stock Exchange of 2008 until periods 2012. Sample did by purposive sampling method. With the sampling method is obtained samples used in this research were 31 consumer goods companies. Types of data used is secondary data of Indonesian Capital Market Directory (ICMD). Analysis technique used in this research is the technique of multiple linear regression analysis. The results of this research are show that in simultan, Debt to Equity Ratio (DER), Net Profit Margin (NPM), Qiuck Ratio (QR), and Insider Ownership are influance toward firm value, as parcial only Net Profit Margins (NPM) is significant effect on firm value.Keywords : DER, NPM, QR,Insider Ownership and Firm Value